Cluster analysis of separate indicators of the banking systems of North Macedonia, the EU Member States and the Balkan countries - Emilija Stojanova Ivanovska (Journal of Contemporary Economic and Business Issues, 2020)
In this paper, a multivariate analysis of the computer statistics, i.e. the Cluster analysis of the banking system concentration indicators and the financial intermediation and portfolio quality indicators by applying the complete linkage and the Ward's linkage method are presented. The main idea is to find out whether the level of banking system concentration and degree of financial intermediation in banking system of North Macedonia is similar or closer to any of the EU Member States or the Balkan countries. Furthermore, since the appropriately modified analyses were performed also with the structural indicators of the banking system and results obtained 10 years ago, the objective is to see whether there are any positive shifts in the similarity of the analysed characteristics of the banking system in North Macedonia to a particular country or group of countries. In the conducted cluster analysis made by applying the method of complete linkage to the indicators of concentration of the banking sector, North Macedonia is grouped first with the Slovak Republic and then with Croatia which means that the similarity of the values of these indicators of these countries is the largest. Regarding the outcome of the second cluster analyses, of the indicators of financial intermediation and portfolio quality by using two comparative clustering methods, North Macedonia is grouped with Montenegro in the penultimate cluster and then this cluster is grouped with Serbia, which confirms that the level of financial intermediation in these Balkan countries is lower compared to the EU Member States, but on the other side the quality of the portfolio is good.
Keywords: F41; G21; G10; N10; O11; 330; banking system; concentation indicators; indicators of the degree of financial intermediation; Cluster Analysis; North Macedonia